2020
DOI: 10.2196/15520
|View full text |Cite
|
Sign up to set email alerts
|

An Eight-Week, Web-Based Mindfulness Virtual Community Intervention for Students’ Mental Health: Randomized Controlled Trial

Abstract: Background Innovative interventions are needed to address the increasing mental health needs of university students. Given the demonstrated anxiolytic and antidepressant benefits of mindfulness training, we developed an 8-week, Web-based Mindfulness Virtual Community (MVC) intervention informed by cognitive behavioral therapy (CBT) constructs. Objective This study investigated the efficacy of the MVC intervention in reducing symptoms of depression, anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 62 publications
1
74
0
1
Order By: Relevance
“…The mean depression scores of participants declined from the high end of mild depression to the low end. The intervention had no effect on stress levels (PSS), although a previous pilot MVC study showed significant reductions in stress levels in a similar population [ 29 ]. One reason for the absent effect could be higher baseline stress scores for this sample than in the pilot study (eg, 20.6 vs 19.2), which was possibly a consequence of several months of a strike that our sample experienced prior to start of Fall 2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean depression scores of participants declined from the high end of mild depression to the low end. The intervention had no effect on stress levels (PSS), although a previous pilot MVC study showed significant reductions in stress levels in a similar population [ 29 ]. One reason for the absent effect could be higher baseline stress scores for this sample than in the pilot study (eg, 20.6 vs 19.2), which was possibly a consequence of several months of a strike that our sample experienced prior to start of Fall 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The topics of the 12 modules and the video duration (average durations of male voice and female voice videos) are presented in Table 1 . The role played by the online mindfulness moderator evolved over time across a pilot study conducted in Winter 2017 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of the internet , mobile phones, and smartphones [36,[38][39][40][41][42][43] for health purposes has been well documented in research. It has been used to address chronic disease management [44,45], mental health challenges [46,47], and hospital readmissions [48], encompassing applications that target the public (i.e., public health informatics), interactions between patients and healthcare professionals, and applications for individual use through smartphone apps (i.e., consumer health informatics). However, little is known about the use of ICTs in the context of violence against women, and only a few articles on the subject have been published recently [43,49,50].…”
Section: Introductionmentioning
confidence: 99%